PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DAN BUDAYA MADRASAH TERHADAP KINERJA GURU MTs NEGERI DI KABUPATEN JENEPONTO - Risnawati, Risnawati; Arismunandar, Arismunandar; Wahira3, Wahira; Zainuddin, M. Said (Jurnal Bimbingan dan Konseling Borneo, 2023)
This study is quantitative research that aims to determine whether there is an influence: 1) transformational leadership of madrasah principals on teacher performance; 2) madrasah culture on teacher performance; 3) transformational leadership of madrasah principals and madrasah culture on teacher performance. The population in this study were all MTs teachers Negeri in Jeneponto Regency which is 239 people, while the sample is 150 people. The research data were obtained through questionnaires. The data analysis technique used is descriptive and inferential data analysis. Based on the results of inferential statistical analysis obtained: 1) the significance value (Sig.) of 0.012 is smaller than the probability of 0.05 and the calculated t value of 2.549 is greater than t table 1.976 which means that there is an effect of transformational leadership of madrasah principals (X1) on teacher performance (Y); 2) the significance value (Sig.) of 0.000 is smaller than the probability of 0.05 and t count of 7.281 is greater than t table 1.976 which means that there is an effect of madrasah culture (X2) on teacher performance (Y); 3) the significance value (Sig.) of 0.000 is smaller than the probability of 0.05 and t count of 7.281 is greater than t table 1.976 which means that there is an effect of madrasah culture (X2) on teacher performance (Y); 3) the significance value (Sig. ) of 0.000 is less than the probability of 0.05 and F count 87.857 is greater than F table 3.06 so it can be concluded that there is an effect of transformational leadership of madrasah principals (X1) and madrasah culture (X2) together on teacher performance (Y) MTs. Negeri in Jeneponto Regency